Elucidating the relationship between hydration and ice recrystallization inhibition with c-linked antifreeze glycoproteins - Czechura, Pawel (University of Ottawa (Canada), 2009)
Antifreeze glycoproteins (AFGPs) are a subclass of biological antifreezes isolated from Atlantic and Antarctic Telost fish. At subzero temperature environments, these compounds have the ability to inhibit ice crystal growth and protect these organisms from cryoinjury and death. The native AFGPs show considerable promise as novel cryoprotectants, however, their limited bioavailability, cytotoxicity and inherent chemical and biological instability have precluded their widespread use. Consequently, rationally designed, non-toxic and stable AFGP analogues became an attractive synthetic challenge. While structural modifications made in previously synthesized C-linked AFGP analogues addressed these issues, further SAR studies were required to elucidate the key structural features necessary for potent inhibitors of ice recrystallization. The SAR studies described in this dissertation verify that hydration is related to ice recrystallization inhibition of the C-linked AFGP analogues. The role of hydration in modulating solution conformation, molecular recognition and biological activity of oligosaccharides, proteins and nucleotides is widely recognized but is often neglected when investigating many biological processes such as the mechanism by which biological antifreezes inhibit the growth of ice. In chapter 3, we have investigated the relationship between carbohydrate configuration and recrystallization-inhibition (RI) activity of functional C-linked AFGP mimetics. The presented results suggest that the configuration of the carbohydrate moiety in C-linked AFGP analogues is extremely important and modulates recrystallization-inhibition activity. It seems likely that differences in hydration for each C-linked pyranose alter the compatibility of the carbohydrate moiety with the three-dimensional hydrogen-bonded network of supercooled bulk water. Consequently, the energy associated with transferring a water molecule to the ice lattice changes and can result in inhibition of ice growth. The study of hydration has been extended and in chapter 4 the first synthesis of C-linked AFGP analogues containing disaccharides has been presented. A method for estimating hydration indices for the glycopeptides was developed and used to rationalize recrystallization inhibition activity trends. The results signify that the relative hydration of the C-linked AFGP analogues directly correlates to the degree of their recrystallization-inhibition activity. Moreover, it was demonstrated that hydration of the AFGP mimetics can be estimated prior to their synthesis. This indicates that superior inhibitors of recrystallization may be engineered based on their predicted hydration. The hydration model developed in chapter 4 was applied to explain RI results presented in chapter 5. It has been established that C-2 N-acetyl moiety of the carbohydrate and the L-alanine residues of the polypeptide backbone improve the RI activity of the C-linked AFGP analogues. Incorporating beta-D-Gal-(1-->3)-D-Ga1NAc into our C-linked AFGP mimetics demonstrated that challenging custom synthesis of carbohydrates is not necessary to obtain a potent recrystallization inhibitor. Analogue containing beta-D-Glc-(1-->3)-D-Ga1NAc proved that stereochemistry of the terminal carbohydrate is very important for RI activity and is optimal when it matches that of galactose. The C-2 N-acetyl moiety of the carbohydrate was shown to influence conformation, thus hydration and consequently recrystallization inhibition property of the C-linked AFGP analogues.
Keywords: Chemistry, Biochemistry.